Wave-absorbing material

Through the composite structure of the metal reflection base layer, the absorbing intermediate layer and the scattering upper layer, combined with the absorption and scattering mechanism, the problem of limited frequency range of traditional absorbing materials is solved, the wide-frequency stealth effect is achieved, and the radar scattering cross-section is reduced.

CN120547853APending Publication Date: 2025-08-26张帆
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510669250.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Traditional absorbent materials have limited frequency range and large thickness, which is difficult to meet the stealth needs of modern multi-band and multi-station radar detection, and a single absorption or scattering mechanism is difficult to meet the broadband stealth requirements.

Method used

The composite structure of the metal reflection bottom layer, the absorbing intermediate layer and the scattering upper layer is adopted. The intermediate layer is made of composite material of iron tetroxide-loaded reduction graphene oxide and epoxy resin. The scattering upper layer is made of chopped carbon fiber reinforced epoxy resin to form a patterned metasurface structure. Combined with the absorption and scattering mechanism, the reflection energy weakening and offset within the range of 2-18GHz is achieved.

Benefits of technology

The coordinated work of broadband absorption and directional scattering is realized, the radar scattering cross-section is reduced, and the complex detection environment of multi-angle and multi-band bands is adapted to the complex detection environment of multi-angle and multi-band bands is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120547853A_ABST
    Figure CN120547853A_ABST
Patent Text Reader

Abstract

The invention provides a wave-absorbing material, and belongs to the technical field of electromagnetic wave absorption. The wave-absorbing material comprises a metal reflection bottom layer, a wave-absorbing middle layer and a scattering upper layer, the wave-absorbing middle layer is made of a ferroferric oxide loaded reduced graphene oxide and epoxy resin (Fe3O4 (at) RGO / EP) composite material and used for absorbing electromagnetic wave energy, and the scattering upper layer is of a patterned metasurface structure made of chopped carbon fiber reinforced epoxy resin (SCF / EP). And a phase-regulated two-dimensional periodic array is formed. By arranging a three-layer structure of the metal reflecting layer, the Fe3O4 (at) RGO / epoxy composite wave-absorbing layer and the chopped carbon fiber scattering layer, broadband absorption and directional scattering control of electromagnetic waves within the range of 2-18 GHz are achieved, a stealth function composite material system with dissipation and deflection dual-mechanism cooperative work is formed, the structure utilizes the patterning design of the scattering layer, and the structure has the advantages that the structure is simple, the structure is compact, and the application range is wide. On the basis of the generalized Snell's law, engineering regulation and control of the radar wave reflection direction are achieved by regulating and controlling the reflection phase difference between pattern units, reflection energy is effectively deviated from the main lobe direction of a radar receiver, and therefore the reflection signal intensity of a target in a radar detection system is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of forming machines, and in particular to a wave-absorbing material. Background Art

[0002] Electromagnetic absorbing materials, as one of the means of stealth technology, are currently the main way to achieve equipment stealth. Radar cross section is an important indicator to measure stealth performance. Therefore, how to reduce RCS has become a research focus in stealth technology.

[0003] Generally speaking, there are two ways to improve the stealth properties of materials: first, electromagnetic waves incident on the surface of an object are absorbed or converted by the absorbing material on the surface of the object, reducing reflection and thus reducing the RCS; second, the abnormal scattering of the metamaterial's metasurface characteristics is used to divert the reflected energy away from the detection radar direction, thereby reducing the RCS at the detection angle. Traditional stealth absorbing materials mainly achieve their stealth performance based on the radar wave absorption mechanism, which makes it difficult to break through the bottleneck of stealth performance. The main problems are as follows:

[0004] (1) Traditional absorbing materials can only absorb a limited range of electromagnetic wave frequencies. To achieve effective absorption, traditional absorbing materials are usually thicker and have a limited scope of application.

[0005] (2) Traditional absorbing materials rely solely on absorbing electromagnetic waves and can generally only achieve good absorbing effects within a specific frequency band, which has significant limitations.

[0006] Most traditional electromagnetic materials convert the energy of incident electromagnetic waves into other energies, which are then lost. This leads to bottlenecks such as narrow bandwidth, large thickness, and high weight. Metamaterials, as artificially designed structures, can break through the limitations of the electromagnetic properties of natural materials and flexibly control the reflection, refraction, and scattering behavior of electromagnetic waves through structural design. Among them, metasurfaces, as two-dimensional metamaterials, have shown great potential in the field of broadband stealth through phase gradients, coding designs, or composite mechanisms. However, a single absorption or scattering mechanism is difficult to meet the stealth requirements of modern multi-band, multi-station radar detection. There is an urgent need to develop composite metamaterials that combine absorption and scattering synergistically. Using traditional materials as a foundation to construct metamaterials can break through the limitations of traditional materials and achieve excellent RCS reduction performance.

[0007] This invention takes broadband microwave stealth metamaterials as the research object, and realizes the expansion of RCS reduction and performance improvement based on the absorption and scattering mechanisms by structural design, arrangement and combination of traditional absorbing materials and composite with metasurfaces. Summary of the Invention

[0008] In order to make up for the above deficiencies, the present invention provides an absorbing material that overcomes the above technical problems or at least partially solves the above problems.

[0009] The present invention is achieved in that:

[0010] The present invention provides an absorbing material, comprising a metal reflective bottom layer, an absorbing middle layer, and a scattering upper layer. The absorbing middle layer is made of a composite material of ferroferric oxide-loaded reduced graphene oxide and epoxy resin (Fe3O4@RGO / EP) and is used to absorb electromagnetic wave energy. The scattering upper layer is made of a patterned metasurface structure of short-cut carbon fiber reinforced epoxy resin (SCF / EP) to form a phase-controlled two-dimensional periodic array. The absorbing middle layer and the scattering upper layer work together to weaken and offset reflected energy in the range of 2-18 GHz, thereby reducing the radar scattering cross section.

[0011] In a preferred embodiment, the intermediate absorbing layer is synthesized by chemical coprecipitation method to synthesize ferroferric oxide nanoparticles loaded on the surface of graphene oxide, and then added with epoxy resin system after vitamin C reduction treatment, and thermally cured to form a composite absorption structure with the ability to simultaneously generate magnetic loss and dielectric loss.

[0012] In a preferred embodiment, the metasurface structure pattern layer is added to the resin in steps by chopped carbon fibers, dispersed by ultrasonic and mechanical stirring, and cured and formed at a constant temperature of 35°C to form preset patterns such as square, circular, diamond, cross and other two-dimensional units, with different reflection phase differences between the units.

[0013] In a preferred embodiment, the phase gradient of the patterned structure is designed according to the generalized Snell's law, satisfying:

[0014]

[0015] Among them, θ r is the reflection angle, θ i is the incident foot, and γ0 is the free space wavelength.

[0016] In a preferred embodiment, the absorbing layer and the scattering layer are connected by direct bonding or an intermediate adhesive layer, and can be laminated in any of the following combinations:

[0017] Structure A: metal-Fe3O4@RGO / EP-SCF / EP;

[0018] Structure B: metal-Fe3O4@RGO / EP;

[0019] Structure C: metal-Fe3O4@RGO / EP--SCF / EP-Fe3O4@RGO / EP;

[0020] Structure D: metal-SCF / EP-Fe3O4@RGO / EP.

[0021] In a preferred solution, the performance parameters of the composite structure include: peak absorption frequency 2-18 GHz, reflection loss RL<-30 dB, effective bandwidth RL<-10 dB≥6 GHz, and RCS reduction rate ≥35%.

[0022] In a preferred solution, the matching relationship between the input impedance and the free space impedance is:

[0023]

[0024] To achieve the optimization of broadband absorption performance.

[0025] In a preferred solution, the structure is covered on the surface of a radar detection sensitive target, which can achieve effective dissipation of electromagnetic wave energy and control of radar reflection direction, and adapt to complex detection environments with multiple angles and multiple frequency bands.

[0026] In a preferred embodiment, the structure has the following adjustable parameter ranges: the absorbing layer thickness d is 1–3 mm, the pattern period p is 5–20 mm, and the phase difference Δφ is controllable within the range of 0°–180° to meet the RCS customization requirements of different combat platforms.

[0027] The present invention provides a wave absorbing material, which has the following beneficial effects:

[0028] 1. By setting up a three-layer structure of a metal reflective layer, a Fe3O4@RGO / epoxy composite absorbing layer, and a chopped carbon fiber scattering layer, broadband absorption and directional scattering control of electromagnetic waves in the range of 2-18GHz are achieved, forming a stealth-functional composite material system with a "dissipation + deflection" dual mechanism working together. Based on the generalized Snell's law, this structure utilizes the patterned design of the scattering layer to achieve engineered control of the radar wave reflection direction by regulating the reflection phase difference between pattern units. This effectively deflects the reflected energy away from the main lobe direction of the radar receiver, thereby reducing the target's reflected signal intensity in the radar detection system.

[0029] 2. By introducing a variety of high-performance functional nanofillers such as BN, SiC, GNP, and MXene, the electromagnetic response and environmental adaptability of the absorbing and scattering layers are comprehensively improved. By introducing ceramic reinforcing fillers such as BN and SiC into the Fe3O4@RGO absorbing matrix, the thermal conductivity and material stability can be improved while enhancing the magnetic polarization response in the low-frequency band, extending the material's absorption capacity for 2-4GHz low-frequency radar waves; and the doping of graphene nanosheets and MXene-type two-dimensional conductive materials further optimizes the dielectric loss path, giving the absorbing layer a higher complex dielectric constant and loss tangent, thereby obtaining a wider effective absorption bandwidth in the 5-15GHz frequency band. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 Schematic diagram of a periodic arrangement model of a super unit structure provided by an embodiment of the present invention;

[0032] Figure 2 A schematic diagram of the metamaterial unit structure provided by an embodiment of the present invention;

[0033] Figure 3 A schematic diagram of a multi-layer structure provided by an embodiment of the present invention;

[0034] Figure 4 A checkerboard arrangement structure with different numbers of super units provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0035] To make the purpose, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.

[0036] Example 1

[0037] Reference Figures 1-4 The present invention provides a technical solution: an absorbing material, comprising a metal reflective bottom layer, an absorbing middle layer and a scattering upper layer, wherein the absorbing middle layer is made of a composite material of ferroferric oxide loaded reduced graphene oxide and epoxy resin (Fe3O4@RGO / EP) and is used to absorb electromagnetic wave energy, and the scattering upper layer is made of a patterned metasurface structure of short-cut carbon fiber reinforced epoxy resin (SCF / EP) and forms a phase-controlled two-dimensional periodic array, and the absorbing middle layer and the scattering upper layer work together to achieve attenuation and offset of reflected energy in the range of 2-18GHz, thereby reducing the radar scattering cross section, the bottom layer and the middle loss layer are squares with a side length a=10.0mm, and the upper layer selects the most common regular pattern for research.

[0038] After the electromagnetic wave is injected, the structure relies on the following two mechanisms:

[0039] Absorption mechanism: Relying on dielectric loss and magnetic loss to dissipate electromagnetic wave energy;

[0040] Scattering mechanism: Relying on phase-controlled metasurface reflective units to deflect reflected waves in a direction, avoiding the radar echo path;

[0041] The matching relationship between the input impedance and the free space impedance is:

[0042]

[0043] To achieve optimization of broadband absorption performance;

[0044] When Z in ≈Z0→Good impedance matching and optimal absorption effect.

[0045] Based on the idea of ​​superposition of absorption and scattering, absorbing materials are combined with metasurfaces with scattering capabilities to form a multi-layer composite structure, and a composite metasurface with dual absorption-scattering mechanisms is designed to see if the loss of electromagnetic waves by absorbing materials and the scattering of electromagnetic waves by metasurfaces can be used together to reduce RCS.

[0046] Using the checkerboard metasurface designed in the previous study, we explored whether multi-layer composite structures can achieve the combined effects of multiple mechanisms, and analyzed the interaction mechanism of a single metasurface and a multi-layer structure of absorber materials. Fe3O4@RGO / EP and metasurfaces were studied.

[0047] The intermediate absorbing layer adopts a chemical coprecipitation method to synthesize ferroferric oxide nanoparticles loaded on the surface of graphene oxide, and then is reduced with vitamin C and then added with an epoxy resin system, and thermally cured to form a composite absorption structure with the ability to simultaneously generate magnetic loss and dielectric loss.

[0048] The metasurface structure pattern layer is added step by step to the resin by short-cut carbon fibers, dispersed by ultrasonic and mechanical stirring, and cured at a constant temperature of 35°C to form preset patterns such as square, circular, diamond, cross and other two-dimensional units, with different reflection phase differences between the units.

[0049] (1) Square pattern: It has a simple configuration and uniform boundary reflection characteristics. According to CST simulation, the reflection phase difference can reach 90° within 6–12 GHz, which is suitable for broadband scattering.

[0050] (2) Circular pattern: It has good rotational symmetry, a smooth phase response under multi-angle incidence conditions, and the phase difference distribution is concentrated between 80°–110°, showing good multi-angle scattering consistency.

[0051] (3) Diamond pattern: It can achieve directional scattering enhancement and exhibits directional scattering function for specific incident angles in simulation. It has a high phase gradient change rate and is suitable for forward suppression of target identification radar signals.

[0052] (4) Cross pattern: The phase difference is more than 120°, which is suitable for strong scattering deflection design. Its high phase gradient can achieve rapid redirection of radar waves when they deviate from the main direction. Simulations show that the maximum angle of scattering direction deviation in the 10–16 GHz frequency band exceeds 45°, significantly reducing radar detectability.

[0053] The specific experimental data are shown in Table 1 below:

[0054] Pattern shape Average reflection phase difference Scattering deflection angle range Effective bandwidth Square 90 20-35 6-12 round 85-105 15-30 5-13 diamond 100-115 25-40 7-14 Cross 120-160 35-50 8-16

[0055] Table 1

[0056] The phase gradient of the patterned structure is designed according to the generalized Snell's law, satisfying:

[0057]

[0058] Among them, θ r is the reflection angle, θ i is the incident foot, and γ0 is the free space wavelength.

[0059] The single unit structures are combined into super units and then arranged periodically. The most common arrangement is a checkerboard pattern, with an array size of 180mm×180mm and a super unit period of 20mm×20mm. Finite element simulation is used to design a metasurface with phase-anomalous reflection. The scattering characteristics are optimized by changing the unit structure combination / arrangement. The unit structures are first combined into super units, and then periodically expanded to obtain a sufficient area for research.

[0060] The absorbing layer and the scattering layer are connected by direct bonding or an intermediate adhesive layer, and can be laminated in any of the following combinations:

[0061] Structure A: metal-Fe3O4@RGO / EP-SCF / EP;

[0062] Structure B: metal-Fe3O4@RGO / EP;

[0063] Structure C: metal-Fe3O4@RGO / EP--SCF / EP-Fe3O4@RGO / EP;

[0064] Structure D: metal-SCF / EP-Fe3O4@RGO / EP.

[0065] The advantages of different compositions of Structure A to Structure D are shown in Table 2 below:

[0066]

[0067]

[0068] Table 2

[0069] This multi-layer structure design allows for flexible selection based on the target frequency band and scattering direction control requirements, enabling customized stealth design. CST simulations show that Structure C exhibits the widest RL <–10dB bandwidth (8GHz) in the 8–14GHz frequency band, while Structure B exhibits optimal RCS suppression directivity.

[0070] The performance parameters of the composite structure include: peak absorption frequency 2-18 GHz, reflection loss RL <-30 dB, effective bandwidth RL <-10 dB ≥ 6 GHz, and RCS reduction rate ≥ 35%.

[0071] The structure is covered on the surface of radar-sensitive targets, can achieve effective dissipation of electromagnetic wave energy and control of radar reflection direction, and adapt to complex detection environments with multiple angles and multiple frequency bands.

[0072] The structure has the following adjustable parameter ranges: the absorbing layer thickness d is 1–3 mm, the pattern period p is 5–20 mm, and the phase difference Δφ is controllable within the range of 0°–180° to meet the RCS customization requirements of different combat platforms.

[0073] Among them, the preparation method of the absorbing intermediate layer is: using the chemical co-precipitation method, the iron salt solution and the GO dispersion are heated in a water bath, NaOH solution is added to adjust to an appropriate pH value, VC powder is added, and the product is separated after a period of reaction, repeatedly washed, and dried to obtain Fe3O4@RGO powder. Weigh an appropriate amount of bisphenol A epoxy resin E51, add an appropriate amount of HHPA and defoaming agent to mix, weigh Fe3O4@RGO according to the required filling amount, add it to the resin system, and disperse it by ultrasonic and mechanical stirring for 30 minutes. Then add an appropriate amount of accelerator 2,4,6-tris(dimethylaminomethyl)phenol, ultrasonically and mechanically stir for 30 minutes to obtain a particle and epoxy resin blend system, and finally use a mold to prepare the Fe3O4@RGO / EP absorbing composite material. Use CST software to simulate the content of the control filler in Fe3O4@RGO / EP to achieve broadband and effective absorption of electromagnetic waves. The most suitable filling amount can be obtained by analyzing the relationship between reflection loss and frequency.

[0074] The scattering upper layer was prepared as follows: To prepare the SCF / EP composite, bisphenol A epoxy resin E51 and curing agent HHPA were first mixed in appropriate proportions to form an epoxy resin matrix. Next, a carbon fiber dispersion process was performed: chopped carbon fibers (SCF) were added to the resin matrix in five batches, with 10-minute intervals between each addition. Mechanical stirring at 500 rad / min and ultrasonic treatment at 500 W were simultaneously applied. The temperature was controlled at 35°C in a water bath. After all fibers were added (a total of 50 minutes), the dispersion process was continued for 2 hours. The accelerator was then added. After adding the desired amount of accelerator, mixing was continued under the same conditions of 35°C, 500 W ultrasonication, and 500 rad / min stirring for 30 minutes. Finally, molding and post-processing were performed. The composite was prepared using a standard curing process, and standard test specimens were prepared using a CNC engraving machine.

[0075] In the actual application process, the traditional electromagnetic absorption mechanism is integrated with the phase-controlled scattering theory to form a composite stealth path in which electromagnetic wave dissipation and reflection path change coexist. When the electromagnetic wave is incident on the surface of the composite structure, it first acts on the topmost patterned scattering layer, which is composed of chopped carbon fiber and epoxy resin. It exhibits different phase response characteristics under specific pattern arrangements (such as square, diamond, cross, etc.). Due to the excellent conductivity of carbon fiber, it forms an induced current in the alternating electromagnetic field, which in turn excites the local secondary radiation field. By reasonably designing the phase difference between each unit pattern, according to the generalized Snell's law, the direction of the reflected electromagnetic wave can be controlled to deviate from the original reflection path, thereby achieving a directional stealth effect. This part not only weakens the radar main beam echo signal, but also directs the scattered energy to other directions, reducing the probability of radar detection of the target;

[0076] After some electromagnetic waves pass through this scattering layer, they further enter the intermediate absorbing layer. This layer uses the Fe3O4@RGO / EP composite material as the absorbing matrix, relying on the magnetic response characteristics of Fe3O4@RGO / EP and the high dielectric loss capacity of RGO to construct an electromagnetic energy dissipation channel. Fe3O4 nanoparticles exhibit excellent hysteresis loss, natural resonance, and eddy current loss characteristics in the GHz frequency band, which can absorb magnetic component energy; while RGO has a rich π electron structure and conductivity, which can absorb electric component energy through mechanisms such as interface polarization and conductivity loss. The synergistic effect of these two gives this layer good complex dielectric parameters and magnetic permeability, which is conducive to wave impedance matching, increases the probability of incident waves entering the interior of the material, and enhances the internal loss effect.

[0077] Different structural combinations (such as structures A / B / C / D) provide functional matching for different application requirements. For example, structure A (metal-Fe3O4@RGO-SCF) is a typical "absorption-scattering" sequence, suitable for radar forward incidence scenarios; structure C (metal-absorber-scatterer-absorber) is a sandwich structure suitable for multi-frequency stealth control; and structure D (scatterer-absorber-scatterer) is more suitable for multi-angle beam incidence environments such as ships.

[0078] Through actual measurements, the structure of this embodiment exhibits excellent broadband absorption capability in the range of 2-18GHz, with a minimum RL value exceeding -30dB, an absorption bandwidth exceeding 6GHz, and an RCS suppression efficiency increased by more than 35% compared to traditional ferrite-based materials. While meeting the absorption requirements, this structure also takes into account lightweight design, pattern adjustability, structural controllability, and processing technology compatibility, making it suitable for large-scale engineering preparation and deployment, and possessing significant practical promotion value.

[0079] Example 2

[0080] On the basis of Example 1, at least one enhanced nano-functional material is further added to the absorbing layer, and the enhanced material is selected from the group consisting of boron nitride (BN), silicon carbide (SiC), graphene nanosheets (GNP), zinc oxide (ZnO), carbon nanotubes (CNT), MXene material (Ti3C2Tx) or polyaniline (PANI) to form a multi-phase synergistic absorbing composite structure to improve the broadband electromagnetic wave absorption performance and thermal stability;

[0081] The nano-reinforced material is doped into the Fe3O4@RGO / EP matrix at a mass fraction of 1% to 10%, and is uniformly dispersed by high-power ultrasound to construct a multi-scale interface polarization path;

[0082] The BN or SiC is a flaky or spherical micro-nanostructure with a particle size controlled between 100nm and 800nm, and is mainly used to enhance the magnetic loss capacity in the low-frequency band, improve thermal conductivity and wave absorption stability under high-temperature conditions;

[0083] The thickness of the absorbing layer is controlled at 2 to 3.5 mm. The addition of the composite reinforcement material will not significantly increase the overall thickness, but can reduce the minimum reflection loss (RL) by more than 3 dB and increase the absorption peak bandwidth by more than 2 GHz.

[0084] The scattering layer is further doped with ZnO or CNT material in the chopped carbon fiber / epoxy system, wherein the ZnO mass fraction is 3% to 8%, which is used to enhance the surface phase gradient control performance and expand the controllable scattering angle;

[0085] The structure has an effective bandwidth greater than 9 GHz with a return loss RL less than –10 dB in the range of 2 GHz to 20 GHz, and a minimum return loss of –35 dB. Compared with the first embodiment, the RCS suppression efficiency is improved by more than 10%, as shown in Table 3.

[0086]

[0087] Table 3

[0088] By introducing enhanced nano-functional fillers into the absorbing and scattering layers, comprehensive improvements in electromagnetic absorption performance, thermal adaptability, mechanical stability, and controllable scattering direction are achieved. When electromagnetic waves encounter dielectric materials, their energy is partially reflected and partially transmitted. If the material possesses appropriate electromagnetic parameters and matches the impedance of free space, the incident energy is maximized within the material. Inside, the wave energy is converted into heat through dielectric and magnetic losses, thereby attenuating the reflected wave.

[0089] Among them, BN / SiC: ceramic dielectric enhances the thermal conductivity and low-frequency magnetic response of the material. BN has a hexagonal flake structure, forming a high interfacial heat conduction channel in the system, suitable for high-temperature working environments; SiC has strong dielectric polarization ability and can form a conductive and dielectric hybrid structure, improving the loss tangent; GNP and MXene: the former is a two-dimensional carbon material with a high specific surface area, which can effectively enhance the real and imaginary parts of the complex dielectric constant, promoting the interfacial polarization and dipole oscillation loss of electromagnetic waves; the latter (such as Ti3C2Tx) is a new two-dimensional material with excellent conductivity and polarity controllability. Its electromagnetic response range is wide and can synergistically achieve broadband absorption characteristics; CNT and ZnO: CNT cooperates with SCF in the scattering layer to form a conductive network structure, while ZnO provides high-frequency response and charge transfer capabilities, further optimizing the reflection direction control in the high frequency band.

[0090] In this embodiment, the peak absorption frequency is controlled by the complex dielectric constant, complex magnetic permeability and material thickness, and its expression is:

[0091]

[0092] When d=3.0mm, μ r =1.9,∈ r =9.0, then:

[0093]

[0094] By adjusting the material thickness and filler ratio, the absorption response of the target frequency band can be precisely controlled to achieve broadband coverage design.

[0095] In this embodiment, the patterned metasurface scattering layer uses chopped carbon fibers as a matrix, and introduces ZnO or CNT to improve its lateral conductivity, thereby achieving phase difference between units. The generalized Snell's law states:

[0096]

[0097] Forming an effective phase gradient per unit length That is, the reflection angle θ can be achieved r The deviation angle of incidence θ i , thereby achieving the purpose of redirecting the direction of electromagnetic waves.

[0098] In cross-shaped, U-shaped, diamond-shaped pattern units, different structures bring different induced current paths, and the control methods are as follows:

[0099] Cross type: The current path is the longest, the inductance effect is obvious, and the phase response is greater than 120°;

[0100] Round: good symmetry, stable reflection, suitable for multi-angle incidence scenes;

[0101] U-shaped: Multi-angle nodes are conducive to surface charge accumulation and are suitable for medium and high frequency bands.

[0102] When the radar wave is incident:

[0103] First, it enters the pattern layer, generating phase difference and primary scattering, then penetrates into the absorbing layer, forming dielectric and magnetic losses. The undissipated energy is reflected by the metal, and then enters the absorbing layer for the second time to be dissipated again. Finally, the residual energy is guided by the pattern layer to deviate from the direction and reflect. Through two incidences, two dissipations, and one round of phase deflection, the dual suppression of radar echo energy and direction is completed.

[0104] In actual use, under the action of electromagnetic waves, the surface of the composite material first receives radar wave signals from the outside, whose waveform is incident on the material surface in a vertical direction or at a specific angle. The outermost layer of the structure of this embodiment is a patterned carbon fiber conductive network. This layer not only has the ability to control the reflection phase, but also forms a local current loop with the assistance of nanofillers (such as ZnO, CNT), realizing the establishment of a stable spatial phase difference between the metasurface units, thereby guiding part of the radar wave to the non-original reflection direction according to the generalized Snell's law, effectively destroying the radar cross-section characteristics of the target, causing the main beam energy to deviate from the radar source, and thus evading detection. In this process, different pattern shapes (cross, circular, U-shaped, etc.) have different coupling modes to the electric field, and the resulting phase response differences are also unique. By designing the pattern array distribution period and size parameters, engineering control of the scattering angle can be achieved, which is suitable for the differentiated requirements of different platforms for the scattering direction. When a part of the electromagnetic wave penetrates the metasurface layer, it will enter the interior of the absorbing layer. This layer is mainly composed of Fe3O4@RGO-based composites and enhanced functional fillers (BN, SiC, GNP, MXene), and its composite structure establishes a three-dimensional multi-scale dielectric environment. First, Fe3O4 particles provide natural magnetic resonance capabilities, and RGO provides efficient dielectric loss paths. The two work together to achieve basic-level electromagnetic wave energy dissipation. Subsequently, the added BN or SiC particles build a high thermal conductivity channel, while enhancing the electromagnetic polarization response in the low-frequency band. The semiconductor properties of SiC further promote the material's tolerance and control width for radio frequency energy. Graphene nanosheets (GNPs) and MXene-type two-dimensional materials (such as Ti3C2Tx) form a dual mechanism of in-plane conductive network and longitudinal interface polarization through their ultra-large specific surface area, abundant polarization sites and high intrinsic conductivity, effectively widening the absorption spectrum in the high-frequency region, increasing the absorption peak and reducing reflection loss;

[0105] The introduction of ZnO and CNT into the scattering layer forms a transverse conductive network structure, which improves the in-plane current control capability in the high-frequency band and enhances the phase accuracy and response width of the pattern structure. Due to its high aspect ratio and intrinsic conductivity characteristics, CNT forms electromagnetic resonance in the microwave region in the frequency response, while improving the flexibility and strength of the scattering layer, making the structure significantly more adherent to complex curved surfaces such as missile fuselages and curved ship skins. Due to its strong polarizability and semiconductor properties, ZnO greatly improves the induced response amplitude to electromagnetic waves, especially in the Ku and X bands, showing good energy dissipation capabilities. The above composite design ensures that this embodiment not only achieves breakthroughs in performance, but also maintains high reliability and high repeatability in complex service environments.

[0106] In terms of thermal stability, the introduction of BN and SiC significantly improves the thermal conductivity of the composite system (>20W / m·K). Even after more than 300 hours of continuous service at 180°C, the reflection loss performance retention rate remains above 95%, meeting the basic high-temperature service life requirements of aviation materials in the national military standard. Furthermore, thermal cycling tests show that after 50 cycles between -40°C and 180°C, the absorption peak shift is less than 0.3 GHz, demonstrating stable interface bonding and low thermal expansion and contraction errors, making it suitable for structural applications in high-altitude, high-speed motion platforms.

[0107] By integrating a nano-reinforced composite material system with a metasurface phase-modulated structure, a novel dual-mechanism absorbing structure has been constructed, combining high-performance broadband absorption, directional scattering, high-stability serviceability, and highly adaptable fabrication. This system demonstrates excellent absorption attenuation and stealth control capabilities across multiple frequency bands, angles, and temperatures. In simulations and experiments, the lowest RL value can reach –35dB, with an absorption bandwidth (RL < –10dB) exceeding 10GHz. The RCS suppression efficiency is over 40% higher than that of conventional Fe3O4 materials, demonstrating outstanding technological advancement and practicality in the field of electromagnetic functional materials.

Claims

1. A wave absorbing material, characterized in that: It includes a metal reflective bottom layer, an absorbing middle layer and a scattering upper layer. The absorbing middle layer is made of a composite material of ferroferric oxide loaded reduced graphene oxide and epoxy resin (Fe3O4@RGO / EP) and is used to absorb electromagnetic wave energy. The scattering upper layer is made of a patterned metasurface structure made of short carbon fiber reinforced epoxy resin (SCF / EP) and forms a phase-controlled two-dimensional periodic array. The absorbing middle layer and the scattering upper layer work together to weaken and offset the reflected energy in the range of 2-18GHz, thereby reducing the radar scattering cross section.

2. The absorbing material according to claim 1, characterized in that: The intermediate absorbing layer adopts a chemical coprecipitation method to synthesize ferroferric oxide nanoparticles loaded on the surface of graphene oxide, and then is reduced with vitamin C and then added with an epoxy resin system, and thermally cured to form a composite absorption structure with the ability to simultaneously generate magnetic loss and dielectric loss.

3. The absorbing material according to claim 2, characterized in that: The metasurface structure pattern layer is added step by step to the resin by short-cut carbon fibers, dispersed by ultrasonic and mechanical stirring, and cured at a constant temperature of 35°C to form preset patterns such as square, circular, diamond, cross and other two-dimensional units, with different reflection phase differences between the units.

4. The absorbing material according to claim 3, characterized in that: The phase gradient of the patterned structure is designed according to the generalized Snell's law, satisfying: Among them, θ r is the reflection angle, θ i is the incident foot, and γ0 is the free space wavelength.

5. The absorbing material according to claim 4, characterized in that: The absorbing layer and the scattering layer are connected by direct bonding or an intermediate adhesive layer, and can be laminated in any of the following combinations: Structure A: metal-Fe3O4@RGO / EP-SCF / EP; Structure B: metal-Fe3O4@RGO / EP; Structure C: metal-Fe3O4@RGO / EP--SCF / EP-Fe3O4@RGO / EP; Structure D: metal-SCF / EP-Fe3O4@RGO / EP.

6. The absorbing material according to claim 5, characterized in that: The performance parameters of the composite structure include: peak absorption frequency 2-18 GHz, reflection loss RL <-30 dB, effective bandwidth RL <-10 dB ≥ 6 GHz, and RCS reduction rate ≥ 35%.

7. The absorbing material according to claim 6, characterized in that: The matching relationship between the input impedance and the free space impedance is: To achieve the optimization of broadband absorption performance.

8. The absorbing material according to claim 7, characterized in that: The structure is covered on the surface of a radar-sensitive target, which can achieve effective dissipation of electromagnetic wave energy and control of radar reflection direction, and adapt to complex detection environments with multiple angles and multiple frequency bands.

9. The absorbing material according to claim 8, characterized in that: The structure has the following adjustable parameter ranges: the absorbing layer thickness d is 1–3 mm, the pattern period p is 5–20 mm, and the phase difference Δφ is controllable within the range of 0°–180° to meet the RCS customization requirements of different combat platforms.

Citation Information

Cited By

  • Radar wave absorbing material and preparation method and application thereof

    CN121906138A

  • A radar wave absorbing material, a preparation method and application thereof

    CN121906138B